The extent of young adult and adult delinquency in poland in the years 1958-1962 on the basis of judicial statistics (Archives of Criminology, 1965)
In the years 1958-1962 a certain slight increase of adult delinquency (until 1960) and later its slight decline has become apparent. This is affirmed by police statistics (relating to the number of crimes registered and revealed by the police), by the data of the  Public Prosecutor's Office (containing information on reported crimes) and by the data of Law Courts (containing the number of convictions).In the years 1958-1962 the yearly number of convictions amounted to about 300 thous. This constitutes an increase of about 70 per cent as compared with the level of 1951 which however was due partly to an enlargement of the competence of Iaw courts.The frequency of convictions of adults measured by the delinquency coefficient (calculated per thousand of criminally liable persons i.e. persons over 17 years of age) amounted to a level of 17,2 in 1960 i.e. 62 per cent higher than in 1951. In 1962 that frequency was expressed by the coefficient 15.5 which indicated an average of 1 conviction on 65 criminally liable persons.Among the total of persons convicted by the Courts of Law juveniles under 17 years of age formed only a very small group (5-9 per cent), nevertheless, together with the young adults (17-20 years of age) they already constituted about 20 per cent of all the convicted. Persons under 30 (practicalły those aged 10-29) constituted half of the total of juveniles found guilty and convicted adults.Poland, together with Yugoslavia and Hungary, seems to belong to that group of countries where against the background of adult delinquency the juvenile and young adult delinquency does not, according to statistics relating to convictions, present a particularly serious problem. In a series of countries, persons under 20-21 years of age constituted more than a half of revealed offenders (e.g. England and Wales, Canada) and in some of them even two thirds of the total (Ireland, Norway, Sweden).Delinquency coefficients denoting frequency of convictions indicate that its degree was highest among the young adults (i.e. those aged 17-20) and adults aged 21-24 and 25-29. In 1962 approximately every 41 person in each of these age groups was convicted.A small increase of the frequency of convictions which occurred in 1958-1960 was most strongly reflected by the convicted of precisely those age groups. Its subsequent decline was there the least noticeable.Out of the total of 300 thous. persons convicted in 1962 about 245 thous. were men and about 55 thous. women. The number of convicted women in relation to 100 convicted men was continually diminishing (though not without certain oscillattions): it was 35 in 1951 and only 22 in 1962.Poland together with Yugoslavia and Hungary, also with Belgium, belongs to the countries with a high percentage of women among the convicted adults (about 20 per cent of the total). In most countries it is much lower and does not even reach 10 per cent (e.g. Norway, Finland, Sweden, Canada, France).The frequency of convictions of men was expressed by the coefficient 29.2 in 1960, which indicates a 70 per cent increase as compared with 1951. It was merely 9 per cent lower than in 1937 (the coefficient was then 31.5). In 1962 the delinquency coefficient for men amounted to 27.0. In that year there was on the average one conviction on 36 criminally liable men.The frequency of convictions of women was expressed by the coefficient 5.3 in 1962 which indicates a mere 2 per cent increase as compared with 1951. In the years 1958-1959 that degree of frequency was however much higher. The coefficient has then reached the level of 6.9 and was even higher than in 1937 when it amounted to 6.6.Among the total of men convicted by the law courts the juveniles constituted 6-10 per cent and together with young adults 20-22 per cent in the years 1958-1962. The percentage of women among the convicted bareIy amounted to 2-4 per cent and 12-13 per cent. Half of the convicted men was somewhat under thirty and half of the women under thirty five years of age. Among the convicted men hardly every tenth man was fifty years old or over. Among the convicted women every sixth one was of that age.The relation between the number of convicted men and women differed in particular age groups: in 1962 there were 15 women to 100 convicted men aged 17-20, 17 to 100 aged 25-29 years, 27 to 100 aged 35-39, 32 to 100 aged 45--49 and 48 to 100 aged 60 and over.Frequency of convictions of juveniles and young men reached a very high level in the course of the period under investigation. In the years 1960-1962 one out of every 23 men aged 17-29 was convicted. Delinquency coefficients for men in older age groups (over 30 years of age) were rapidly diminishing; the value of the coefficients for men aged 35-39 equalled two thirds of the value of the coefficienits for the 17-20 age group, about a half for the 45-49, about one third for the 50-59 and about one eighth for the age group of sixty and over.The highest frequency of convictions of women occurred among those aged 21-24. It was higher among women of 40 or even 45 than among those aged 17-20. The decline in the frequency of convictions of women over 50 was relatively twice lower than that of men.In a series of European countries various groups of juvenile and not adult offenders have the highest delinquency coefficient, as for example in England and Wales, Norway and Sweden. In other countries, among which beside Poland and Hungary also German Federal Republic and Switzerland should be counted, the maximum degree of frequency of convictions concerns various age groups of adults in the young groups of age.Analysing frequency of convictions occurring in various areas of the country one can theoretically use two kinds of coefficients: calculated according to the place of crime perpetrated by the convicted person, and according to the place of residenoe of the convicted person.Differences, existing between estimates of frequency of delinquency based on these coefficients present themselves as follows: they are of no particular importance when all-country data are examined, they are of some slight importance in case of particular voivodships, of greater importance when frequency of convictions in town and oountry is being defined and of prirnary importance at estimating that frequency of convictions in town and country in particular voivodships and in most of the 22 largest towns in Poland.Coefficients, based on the data relating to the place of crime, indicated in many voivodships larger differences in the degree of frequency of convictions in town and country than the coefficients based on the data relating to the domicile of the convicted persons. Although the town becomes the place of crime much more often than the countryside, the difference between the "criminality" of the town and village dwellers is rather small. The extent of differences between estimates of frequency of convictions in town and country in particular voivodships based on both those coefficients proved to be correlated with the extent of daily travels to and from work in these voivodships. Also analogous differences between estimates of frequency of convictions in the 22 largest towns in Poland were connected with extent of daily travels to work.In 1951 the delinquency coefficient for adults in the town (14.7) was 86 per cent higher than in the countryside (8.0). In 1962 the coefficient in the town (18.1) was already only 41 per cent higher than in the countryside (12.8). The general increase of the frequency of convictions which occurred in the last twelve years period was more influenced by its changes in the coutryside than in the town.In the years 1959-1962 one out of 30-32 men and one out of 115-149 women was convicted in town, while one out of 39-44 men and one out of 189-256 women was convicted in the country.In 1960 every twentieth man at the age of 17-20 was convicted in town.The frequency of convictions of 17-20 year olds definiteiy dominated over the frequency of convictions of other groups of adults only in the case of men in towns; as regards men in the countryside that preponderance was slight. In towns the frequency of convictions of women aged 17-20 was somewhat lower than of those aged 21-24 and in the country definitely lower than the frequency of convictions of all older women (even 45-49 years old).In 1960 the delinquency coefficient for men (29.2) was 4.4 times higher than the delinquency coefficient for women (6.6) and the differences in frequency of convicted men and women were smaller in town than in the country. Largest diffenences in the frequency of convictions of men and women were noted among those aged 17-20, convicted for offences committed in the country, and the smallest occurred among the oldest convicted who committed offences on the town.Differences in the frequency of convictions between town and country as well as between men and women, were smaller in western and northern territories than in the remaining areas of the country. Also the delinquency coefficients were higher in western and northern territories than in other areas.A proper analysis of factors determining differences in the frequency of convictions of adults in different areas is particularly complicated. It seems that putting forward and verifying the hypotheses which explain the constantly occurring differences in coefficients calculated for particular voivodships, ought to take place not in connection with an analysis of data relating to all convicted adults jointly but separately for those convicted for certain categories or groups of offences, separately for men and women and separately for different age groups.A relationship has been ascertained in the regional distribution of men and women delinquency, and that in all age groups; it was very strong regarding the relatively younger convicted (viz. higher, medium and lower degree of the frequency of convictions regarding both men and women appeared as a rule in the same voivodships). That relationship was weaker in the older groups.An analysis of the regional repartition of the frequency of convictions of men convicted in different age groups has shown that this repartition was most similar in case of persons belonging to the neighbouring age groups and diminished in those farther apart. As regards persons aged 60 and over this repartition somewhat differed from that encountered in other age groups. The same correlations even more strongly marked, applied also to women.Taking into consideration coefficients for the total of adults, it has been stated that in the years 1951, 1955, 1957 and 1960 a relatively higher degree of frequency of convictions continually appeared in western territories and in the Katowice voivodship (moreover, in Warsaw and Łódź). Also relationships between the regional differentiation of frequency of convictions and migration of the population have been established, their appearance being due both to the last war and its consequences as well as to the industrialization and urbanization of the country.The distribution of frequency of convictions (in particular voivodships) contains statistical tables concerning, among others, the structure of dela statistically significant similarity.Numerous statistical tables concerning questions briefly outlined in the sumrnary are included in the text of the author's work. The annex contains statistical tables concerning among others, the structure of deliquency and recidivism.